Alkali‐Treated Mg–Al Layered Double Hydroxides for General Use: Oxidative Polymerization, Metal and Nanocarbon Oxidation, and Catalytic Decomposition of Pollutants. Issue 23 (8th October 2018) - Han, Nara; Kaang, Byung Kwon; Choi, Won San
Abstract: An alkali‐treated Mg–Al layered double hydroxide (A‐LDH) is prepared by NaOH treatment of normal Mg–Al LDH (N‐LDH) at high temperature. Four NaOH treatments are performed with N‐LDH to control the basicity of the LDHs. Among the four A‐LDHs, the A‐LDH possessing a certain basicity shows several unique characteristics that are not observed in N‐LDH. The A‐LDH induces a controlled oxidative polymerization of dopamine into spherical polydopamine (Pdop) particles and can effectively oxidize metals (Cu and Al) and nanocarbons (carbon nanotubes (CNTs) and graphite) to produce oxidized CNTs and oxidized/exfoliated graphene oxide with excellent dispersibility. These interesting phenomena are tested by simply mixing the compounds with A‐LDH at room temperature without an energy‐consuming process and toxic chemicals. Furthermore, A‐LDH exhibits excellent catalytic performances for the degradation of organic pollutants such as various azo dyes. Abstract : In this paper alkali‐treated Mg–Al layered double hydroxides with a controlled basicity that can quickly initiate oxidative polymerization, effectively oxidize metals and nanocarbons, and catalyze the decomposition of various azo dyes without using toxic chemicals and a high energy‐consumption process are reported.